On the angle between two subspaces of an inner product space - Hendra Gunawan (Hilbert Journal of Mathematical Analysis, 2025)
In this paper, we shall discuss two formulae for the angle between two subspaces, or more generally the angle from a subspace of dimension $p$ to another subspace of dimension $q$ with $1\le p\le q\le \dim(X)$, in an inner product space $X$. In particular, we shall see that the two seemingly different formulae, one is obtained by H. Gunawan, O. Neswan, and W. Setya-Budhi in 2005 and the other by N. Wildberger in 2017, are actually identical.